The Impact of Village Funds on Village Electrification in Indonesia - Sari, Adhe Novita; Yudhistira, Muhammad Halley (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
As an archipelagic country with a dense population, Indonesia develops a huge gap in development of economic, social etc in the urban and rural area. One of the disparity is in providing electricity. This study aims to analyze the effect of village funds on village electrification in Indonesia.  The study examines the correlation between village funds for the provision of infrastructure and the acceleration of village electrification with the method of quantitative descriptive approach with a panel data regression method with a fixed effect model. The result of the study shows that village funds are positively correlated with village electrification in Indonesia. It says that every 1% increase in village funds is completely correlated with a 0.98% increase in village electrification ratio. Other results show that the influence of village funds on increasing electrification is seen to be higher in villages outside Java and the coastal region. Although village funds are not intended directly to increase village electrification in Indonesia, the study concludes that village funds can be a catalyst for increasing electrification ratios in areas with basic infrastructure needs.